Utilization Of Content-Based Filtering Method In Game Recommendation With Support Vector Machine Algorithm - Indra Yustiana; Ivana Lucia Kharisma; Ade Arian (Komunitas Dosen Indonesia, 2025)
The explosive growth of the gaming industry has led to a